Konsep Musibah Dalam Surat An-Nisa [4]: 79 (Kajian atas tafsir MĀ Aṣābaka karya K.H. Yasin Asmuni) - M. Husni Makki (Kartika: Jurnal Studi Keislaman, 2026)
This study examines K.H. Yasin Asmuni's interpretation of the concept of calamity (muṣībah) in QS. An-Nisā’ verse 79 through his work Tafsir Mā Aṣābaka. Employing a qualitative library research method with a descriptive-analytical approach, this research aims to explore the theological and ethical constructs within this local pesantren exegesis. The findings reveal that K.H. Yasin Asmuni interprets ḥasanah (goodness) as God’s grace and bounty, while sayyi’ah (evil or calamity) is understood as a consequence of human actions, sins, or negligence. This interpretation integrates the perspectives of Ahlus Sunnah and Mu’tazilah, emphasizing both divine will and moral responsibility. The work heavily references ar-Rāzī’s Mafātīḥ al-Ghayb and is presented in Arabic with Pegon script (Javanese written in Arabic characters), reflecting the acculturation of Islam with local Nusantara culture. The main contribution of Tafsir Mā Aṣābaka to the treasury of Indonesian exegesis lies in its reinforcement of a balanced theological understanding between God’s decree and human agency as well as its relevance as spiritual education and mental reinforcement for communities frequently facing disasters.